Actualization of Pancasila as an Integrative Paradigm in Forming Imagination and Creativity - Suud Sarim Karimullah (Pancasila: Jurnal Keindonesiaan, 2023)
The modern paradigm of science and technology with various metaphysical and ethically neutral approaches has dragged the millennial generation to the aridity and need for dimensions of thinking, so it is urgent if Pancasila is used as an integrative paradigm in the formation of imagination and creativity to increase self-awareness that the guideline of life in the nation and state in Indonesia is Pancasila. This research uses a qualitative method with a content analysis approach to gathering relevant information related to the topic or problem of this study. The results of this study state the importance of actualizing the values of Pancasila in praxis life because there is constantly changing and renewal in transforming the values of Pancasila into norms and practices of life while maintaining consistency, relevance and contextualization. Pancasila, as an integrative paradigm in the formation of imagination and creativity among the millennial generation in the development of Science and Technology, especially for the life of society, nation and state, is expected to be the basis and roots of scientific development that is adjusted to the cultural values of the Indonesian people so that the development of science and technology does not get out of the values that the Indonesian people have. However, this must also be supported by various competencies that must be honed and cultivated, such as critical thinking, creativity, innovation, communication, and collaboration among the millennial generation.